2008
DOI: 10.1029/2007ja012965
|View full text |Cite
|
Sign up to set email alerts
|

First results from the Cassini radio occultations of the Titan ionosphere

Abstract: The first four sets of radio occultations of the Titan's ionosphere were obtained by the Cassini spacecraft between March 2006 and May 2007. These occultations occurred at middle and high latitudes, at solar zenith angles from about 86° to 96°. The main ionospheric peak was seen, as expected from modeling and previous observations, near 1200 km, with a density of about 1–3 × 103 cm−3. A consistent ledge near 1000 km was also seen, and one of the polar observations found a significant (∼3 × 103 cm−3) layer in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 40 publications
7
70
1
Order By: Relevance
“…This shows for the first time an integrated computation from 0 to 1600 km due to three different sources with a coupling through the secondary electron transport. Although this curve cannot be compared in terms of intensity to the nightside measured electron density profiles published in Kliore et al (2008) (because the effective coefficient rate varies with altitude), the global shape can still be compared. At night, the measurements show a layer around about 500 km.…”
Section: Full Height Profile and Comparison With Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This shows for the first time an integrated computation from 0 to 1600 km due to three different sources with a coupling through the secondary electron transport. Although this curve cannot be compared in terms of intensity to the nightside measured electron density profiles published in Kliore et al (2008) (because the effective coefficient rate varies with altitude), the global shape can still be compared. At night, the measurements show a layer around about 500 km.…”
Section: Full Height Profile and Comparison With Datamentioning
confidence: 99%
“…The radio experiment onboard Cassini allowed retrieval of the ion densities down to 200 km (Kliore et al 2008). Computing the ion densities from the ion production necessitates a full chemistry code, which is not available in the present work.…”
Section: Full Height Profile and Comparison With Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Atreya 1986; Gan et al 1992;Cravens et al 2008 and references therein) and it has also been suggested as a source of the ionosphere observed by Cassini during T5 (Cravens et al 2006;Agren et al 2007). Cravens et al (2008) also suggested that precipitation of energetic protons and oxygen ions from Saturn's magnetosphere into the atmosphere is an important source at lower altitudes (≈ 500 -800 km) and might explain the ionosphere observed at these altitudes by the Cassini Radio Science (RSS) experiment (Kliore et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Solar radiation and energetic plasma from Saturn's magnetosphere ionizes the neutral molecules in Titan's ionosphere, creating an ionosphere at altitudes above about 400 km (Bird et al 1997;Wahlund et al 2005;Young et al 2005;Keller et al 1992;Gan et al 1992;Galand et al 1999;Banaskiewicz et al 2000;Molina-Cuberos et al 2001;Lilensten et al 2005a;Agren et al 2007;Cravens et al 2008, Kliore et al, 2008). Titan's neutral atmosphere consists mainly of molecular nitrogen and methane but the relatively minor amounts of many hydrocarbon and nitrogen-bearing species play an important role in the upper atmosphere and ionosphere Vuitton et al 2006Vuitton et al , 2007Fox and Yelle 1997;Keller et al 1998;Waite et al 2007).…”
Section: Introductionmentioning
confidence: 99%